2023
DOI: 10.1186/s40623-023-01771-1
|View full text |Cite
|
Sign up to set email alerts
|

A statistical study of convective and dynamic instabilities in the polar upper mesosphere above Tromsø

Abstract: We have studied the convective (or static) and dynamic instabilities between 80 and 100 km above Tromsø (69.6° N, 19.2° E) using temperature and wind data of 6 min and 1 km resolutions primarily almost over a solar cycle obtained with the sodium lidar at Tromsø. First, we have calculated Brunt–Väisälä frequency (N) for 339 nights obtained from October 2010 to December 2019, and the Richardson number (Ri) for 210 nights obtained between October 2012 to December 2019. Second, using those values (N and Ri), we ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…When GWs break/saturate, they provide atmospheric convection and dynamic instability to the atmosphere. The Brunt–Väisälä frequency N [s −1 ] describes the oscillation frequency of an air parcel in a stable atmosphere; the atmosphere becomes convectively unstable when N 2 becomes negative (Emanuel, 1994; Nozawa et al., 2023). Ji et al.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…When GWs break/saturate, they provide atmospheric convection and dynamic instability to the atmosphere. The Brunt–Väisälä frequency N [s −1 ] describes the oscillation frequency of an air parcel in a stable atmosphere; the atmosphere becomes convectively unstable when N 2 becomes negative (Emanuel, 1994; Nozawa et al., 2023). Ji et al.…”
Section: Methodsmentioning
confidence: 99%
“…When GWs break/saturate, they provide atmospheric convection and dynamic instability to the atmosphere. The Brunt-Väisälä frequency N [s 1 ] describes the oscillation frequency of an air parcel in a stable atmosphere; the atmosphere becomes convectively unstable when N 2 becomes negative (Emanuel, 1994;Nozawa et al, 2023). Ji et al (2022) also suggested an association between N 2 being less than zero and GWB on Mars, so we calculate Brunt-Väisälä frequencies (N) based on neutral atmospheric CO 2 density and take N 2 less than zero as an index of GWB.…”
Section: Calculation Of the Brunt-väisälä Frequencymentioning
confidence: 99%
“…During winter, minimum dissipation rates are observed at approximately 88 km. Nozawa et al (2023) examined convective and dynamic instability probabilities between 80 and 100 km in winter using sodium lidar data from Tromsø, showing in Figure 5 that these probabilities reach their lowest value at around 90 km. This aligns with the winter dissipation rate altitude profile in Figure 3a, suggesting a positive correlation between higher dissipation rates and increased convective and dynamic instabilities.…”
Section: Geophysical Research Lettersmentioning
confidence: 99%